Review—Modeling Methods for Analysis of Electromigration Degradation in Nano-Interconnects. (4th March 2021) - Ceric, H.; Selberherr, S.; Zahedmanesh, H.; de Orio, R. L.; Croes, K.
Abstract : Mitigation of the degradation for down-scaled interconnects requires an in-depth understanding of the failure mechanisms of electromigration and, therefore, the development of adequate simulation models based on this understanding. We present a novel concept for modeling of nano-interconnect structures, the effective domain method, which describes the impact of grain boundaries and grain distribution on the nano-interconnect reliability and how this impact changes with down-scaling of the interconnect width. Furthermore, a simple and numerically efficient approach for modeling of void growth and its influence on nano-interconnect resistivity is presented. Both novel approaches are studied on timely nano-interconnect layouts and discussed in comparison to experimental results. The simulations based on the novel modeling concept predict the reduction of interconnect lifetime with increased temperature and the reduced linewidth, as observed in experiments.